UV photocuring powder treating agent as well as preparation method and application thereof

By using UV photocuring powder treatment agent, the UV photocuring powder treatment agent is formed through the mixing of hydrolysis reaction and photoinitiator, the problem of low powder coating in the prior art is solved, and more thorough powder coating is achieved, and thermal conductivity and product reliability are improved.

CN119798303APending Publication Date: 2025-04-11SUZHOU HI TECH ELECTRONICS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202412000267.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the physical coating process of the powder treatment agent is complicated and the degree of coating of the powder is low, resulting in the bonding strength of the treated powder and the base glue, which affects the thermal conductivity and product reliability.

Method used

The UV photocuring powder treatment agent is used to hydrolyze the first silane coupling agent and the second silane coupling agent to prepare an oligomer powder treatment agent, and mix it with the photoinitiator to form a UV photocuring powder treatment agent. The coating effect of the powder is enhanced by stirring and drying under UV light.

Benefits of technology

Through the use of UV photocuring powder treatment agent, the powder coating is more thorough, reducing the viscosity of the thermal gel, improving fluidity and settlement phenomena, improving thermal conductivity, and enhancing the reliability and life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798303A_ABST
    Figure CN119798303A_ABST
Patent Text Reader

Abstract

The invention discloses a UV photocuring powder treating agent as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing a first silane coupling agent and a second silane coupling agent, and carrying out hydrolysis reaction to prepare an oligomer powder treating agent; wherein the first silane coupling agent comprises any one of a silane coupling agent 171, a silane coupling agent A151 and a silane coupling agent A172 or a combination of more of the silane coupling agent 171, the silane coupling agent A151 and the silane coupling agent A172; the second silane coupling agent comprises a silane coupling agent 570; and uniformly mixing a photoinitiator with the oligomer powder treating agent, so as to prepare the UV photocuring powder treating agent. According to the invention, the UV photocuring powder treating agent is adopted to treat the powder, and can form complexation with hydroxyl groups on the surface of the powder to enhance the binding force and form a certain amount of reticular macromolecules to wrap the powder, so that the powder is coated more thoroughly, the viscosity of the high-thermal-conductivity gel is further reduced, and the fluidity and sedimentation phenomenon of the high-thermal-conductivity gel are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of powder treatment agents, and specifically relates to a UV light-curing powder treatment agent and a preparation method and application thereof. Background Art

[0002] High thermal conductivity gels generally have the characteristics of high viscosity, poor fluidity, and severe sedimentation. These characteristics may lead to uneven filling gaps and uneven distribution, thus affecting thermal conductivity; forming cavities or bubbles inside the heat sink, affecting thermal conductivity and appearance; the sedimentation problem of powders caused by gravity will also affect the heat dissipation effect; the most serious problem may affect the reliability and life of the product. Therefore, when designing and preparing thermal conductive gels, it is necessary to comprehensively consider these factors and take corresponding measures to optimize its viscosity, fluidity, and uniformity.

[0003] In the prior art, powder treatment agents are usually used to improve the compatibility and adhesion of powders and silicone rubber. Generally, the treatment agent is first hydrolyzed with water and alcohol solution, and then stirred and added at a certain temperature. After the addition is completed, vacuum distillation and other treatments are performed at high temperature. For example, a powder treatment agent disclosed in the patent with publication number CN118406237A is such a common operation method, but this method is complicated to operate, and it undergoes a physical coating process, the degree of powder coating is low, and the bonding strength between the treated powder and the base rubber is not high. At present, the prior art uses powder treatment agents to physically coat thermal conductive powders, involving multiple steps, such as dispersion, coating, drying, etc., and requires precise control of the parameters of each process. The operation is complicated and the degree of powder coating cannot be fully controlled. Summary of the invention

[0004] The main purpose of the present invention is to provide a UV light-curing powder treatment agent and a preparation method and application thereof, so as to overcome the deficiencies of the prior art.

[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0006] An embodiment of the present invention provides a method for preparing a UV light-curing powder treatment agent, which comprises:

[0007] The first silane coupling agent and the second silane coupling agent are mixed and subjected to a hydrolysis reaction to obtain an oligomer powder treatment agent; wherein the first silane coupling agent includes any one or more combinations of silane coupling agent 171, silane coupling agent A151, and silane coupling agent A172; and the second silane coupling agent includes silane coupling agent 570;

[0008] And, the photoinitiator is evenly mixed with the oligomer powder treating agent to prepare a UV light curing powder treating agent.

[0009] The embodiment of the present invention also provides a UV light-curing powder treating agent prepared by the aforementioned preparation method.

[0010] The embodiment of the present invention also provides the use of the aforementioned UV light-curing powder treatment agent in treating powder or preparing a high thermal conductivity gel.

[0011] The embodiment of the present invention further provides a powder processing method, which comprises: mixing the powder with the aforementioned UV light-curing powder processing agent and stirring the mixture under UV light conditions, and then drying the mixture to obtain UV light-curing powder.

[0012] The embodiment of the present invention also provides UV light-cured powder obtained by the aforementioned treatment method.

[0013] The embodiment of the present invention further provides a high thermal conductivity gel, which includes: a base glue and the aforementioned UV light-cured powder.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention uses a UV light-curing powder treatment agent to treat the powder, which can form a complex with the hydroxyl groups on the surface of the powder to enhance the binding force, forming a certain amount of network macromolecules to wrap the powder, so that the powder is more thoroughly coated, thereby reducing the viscosity of the thermal conductive gel, improving its fluidity and sedimentation phenomenon; at the same time, due to the improvement in fluidity, more thermal conductive powder can be added to the formula to further improve the thermal conductivity of the gel. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 This is the infrared spectrum of the polymer in the UV light-curing premix in Example 1 of the present invention. DETAILED DESCRIPTION

[0017] In view of the defects of the prior art, the inventors of this case have proposed the technical solution of the present invention after long-term research and extensive practice. It mainly uses a UV light-curing powder treatment agent containing UV light curing. It uses a prepolymer containing UV photosensitive functional groups to further cross-link under the irradiation of UV light to form a comb-like structure. The end of the comb contains carbon-carbon double bonds, which can form a complex with the hydroxyl groups on the surface of the powder to enhance the binding force. The main chain of the comb can form a certain amount of network macromolecules to wrap the powder, making the powder coating more thorough, reducing the viscosity of the high thermal conductive gel, and improving its fluidity and sedimentation.

[0018] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Specifically, as one aspect of the technical solution of the present invention, a method for preparing a UV light-curing powder treatment agent includes:

[0020] The first silane coupling agent and the second silane coupling agent are mixed and subjected to a hydrolysis reaction to obtain an oligomer powder treatment agent; wherein the first silane coupling agent includes any one or more combinations of silane coupling agent 171, silane coupling agent A151, and silane coupling agent A172; and the second silane coupling agent includes silane coupling agent 570;

[0021] And, the photoinitiator is evenly mixed with the oligomer powder treating agent to prepare a UV light curing powder treating agent.

[0022] In some preferred embodiments, the preparation method specifically comprises: mixing the first silane coupling agent and the second silane coupling agent and adding water and alcohol, and then performing a hydrolysis reaction at 60 to 80° C. for 1 to 2 hours to obtain a UV light-curing premixed liquid containing an oligomer powder treatment agent;

[0023] And, the photoinitiator is evenly mixed with the UV light-curing premixed liquid to prepare a UV light-curing powder treatment agent.

[0024] Furthermore, the mass ratio of the first silane coupling agent to the second silane coupling agent is 0.8:1 to 1.2:1.

[0025] Furthermore, the mass ratio of the water to the sum of the first silane coupling agent and the second silane coupling agent is 5 to 15:100.

[0026] Furthermore, the mass ratio of the alcohol to the sum of the first silane coupling agent and the second silane coupling agent is 5-15:100.

[0027] Furthermore, the mass ratio of the photoinitiator to the UV light curing premix is ​​0.1-5.0:100.

[0028] Furthermore, the oligomer powder treating agent has a structure as shown in formula (I):

[0029]

[0030] And / or, the photoinitiator includes photoinitiator TPO and / or photoinitiator 819, but is not limited thereto.

[0031] And / or, the alcohol includes ethanol and / or isopropanol, but is not limited thereto.

[0032] Another aspect of the embodiments of the present invention further provides a UV light-curing powder treating agent obtained by the aforementioned preparation method.

[0033] Another aspect of the embodiments of the present invention further provides the use of the aforementioned UV light-curing powder treating agent in treating powder or preparing a high thermal conductive gel.

[0034] Another aspect of the embodiments of the present invention further provides a powder processing method, which includes: mixing the powder with the aforementioned UV light-curing powder treatment agent and stirring the mixture under UV light conditions, and then drying the mixture to obtain UV light-curing powder.

[0035] In some preferred embodiments, the powder includes any one or more combinations of aluminum oxide, aluminum nitride, magnesium oxide, calcium carbonate, boron nitride, and aluminum hydroxide, but is not limited thereto.

[0036] In some preferred embodiments, the mass ratio of the powder to the UV light-curing powder treating agent is 100:0.1-5.0.

[0037] In some preferred embodiments, the UV light irradiation uses a wavelength of 365-395 nm.

[0038] In some preferred embodiments, the stirring reaction time is 1 to 2 hours.

[0039] In some preferred embodiments, the drying process is carried out at a temperature of 110 to 130° C. and for a time of 30 to 60 minutes.

[0040] In some more specific embodiments, the powder processing method includes:

[0041] (1) preparing UV light curing premix: mixing silane coupling agent 171 and silane coupling agent 570 in a ratio of 1:1 and then hydrolyzing them under the action of alcohol to generate an oligomer powder treatment agent with a certain molecular weight. The amount of water and alcohol added is 5-15wt% of the total amount of the coupling agent;

[0042] (2) Preparation of UV light-curing powder treatment agent: adding a certain amount of photoinitiator to the UV light-curing premix and stirring evenly, the photoinitiator is TPO or 819, and the addition amount is 1 to 3 wt % of the UV light-curing premix;

[0043] Among them, the following reactions occur during the preparation of UV light-curing powder treatment agent:

[0044]

[0045] (3) Powder treatment: Add powder to a reaction kettle, add UV light-curing powder treatment agent while stirring, and stir under UV light. The UV light-curing agent is 0.1 to 5.0 wt % of the powder. Finally, bake in an oven at 130° C. for 30 min to complete the powder treatment.

[0046] Among them, the following reactions occur during the processing of powder:

[0047]

[0048] n can be any natural number from 10 to 50.

[0049] Another aspect of the embodiments of the present invention further provides UV light-cured powder obtained by the aforementioned treatment method.

[0050] Another aspect of the embodiments of the present invention further provides a high thermal conductivity gel, which includes: a base glue and the aforementioned UV light-cured powder.

[0051] In some preferred embodiments, the mass ratio of the base glue to the UV light-curing treated powder is 20:80 to 3:97.

[0052] In some preferred embodiments, the base glue includes any one or more combinations of vinyl silicone oil, methyl silicone oil, alkoxy silicone oil, hydroxy silicone oil, and hydrogen-containing silicone oil, but is not limited thereto.

[0053] In some preferred embodiments, the high thermal conductivity gel further comprises an auxiliary agent; the auxiliary agent comprises a catalyst and / or an inhibitor.

[0054] Furthermore, the catalyst includes any one or more combinations of platinum catalyst, chloroplatinic acid, and peroxide, but is not limited thereto.

[0055] Further, the inhibitor includes TMDO and / or VMC, but is not limited thereto.

[0056] The technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments. This embodiment is implemented on the premise of the technical solution of the invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0057] Unless otherwise specified, the experimental materials used in the following examples can be purchased from conventional biochemical reagent companies.

[0058] Example 1

[0059] (1) Silane coupling agent 171 and silane coupling agent 570 are uniformly mixed in a ratio of 1:1 and then hydrolyzed under the action of alcohol to generate an oligomer powder treatment agent with a certain molecular weight. The amount of water and alcohol added is 10wt% and 5wt% of the total amount of the coupling agent, respectively, to obtain a UV light-curing premixed liquid; wherein the infrared spectrum of the polymer in the UV light-curing premixed liquid is as follows: Figure 1 As shown, 1085.5cm -1 The characteristic absorption peak at is the characteristic absorption peak of Si-O-Si;

[0060] (2) Add a certain amount of photoinitiator TPO to the UV light-curing premixed liquid and stir evenly, wherein the amount of photoinitiator TPO added is 2 wt % of the UV light-curing premixed liquid to prepare a UV light-curing powder treating agent.

[0061] (3) Add a UV light-curing powder treatment agent to powdered alumina (the UV light-curing powder treatment agent is 0.5 wt % of the powdered alumina) at a rotation speed of 70 rpm, stir for 1 hour under UV light conditions, and then bake in an oven at 130° C. for 30 minutes to obtain UV light-cured alumina.

[0062] (4) Vinyl silicone oil (2000 cps) and UV light-cured alumina were mixed in a mass ratio of 20:80 to prepare a high thermal conductivity gel.

[0063] Comparative Example 1

[0064] Vinyl silicone oil (2000 cps) and aluminum oxide were mixed in a mass ratio of 20:80 to prepare a high thermal conductive gel.

[0065] Comparative Example 2

[0066] (1) mixing silane coupling agent 171 and silane coupling agent 570 in a ratio of 1:1 and then hydrolyzing the mixture under the action of alcohol to obtain a hydrolyzed silane coupling agent;

[0067] (2) adding the hydrolyzed silane coupling agent to the powdered alumina (the hydrolyzed silane coupling agent is 0.5 wt % of the powdered alumina) at a rotation speed of 70 rpm, stirring for 30 minutes, and then baking in an oven at 130° C. for 30 minutes to obtain conventional treated alumina.

[0068] (3) Vinyl silicone oil (2000 cps) and conventional treated alumina were mixed in a mass ratio of 20:80 to prepare a high thermal conductivity gel.

[0069] Comparative Example 3

[0070] (1) hydrolyzing the silane coupling agent 171 under the action of alcohol to generate an oligomer powder treatment agent with a certain molecular weight, wherein the amount of water and alcohol added is 10 wt% and 5 wt% of the total amount of the coupling agent, respectively, to obtain a premixed solution;

[0071] (2) Add a certain amount of photoinitiator TPO to the premixed liquid and stir evenly. The amount of photoinitiator TPO added is 2 wt % of the UV light-curing premixed liquid to prepare a UV light-curing powder treatment agent.

[0072] (3) Add a UV light-curing powder treatment agent to powdered alumina (the UV light-curing powder treatment agent is 0.5 wt % of the powdered alumina) at a rotation speed of 70 rpm, stir for 1 hour under UV light conditions, and then bake in an oven at 130° C. for 30 minutes to obtain UV light-cured alumina.

[0073] (4) Vinyl silicone oil (2000 cps) and UV light-cured alumina were mixed in a mass ratio of 20:80 to prepare a high thermal conductivity gel.

[0074] Comparative Example 4

[0075] (1) hydrolyzing the silane coupling agent 570 under the action of alcohol to generate an oligomer powder treatment agent with a certain molecular weight, wherein the amount of water and alcohol added is 10wt% and 5wt% of the total amount of the coupling agent, respectively, to obtain a UV light curing premix;

[0076] (2) Add a certain amount of photoinitiator TPO to the UV light-curing premixed liquid and stir evenly, wherein the amount of photoinitiator TPO added is 2 wt % of the UV light-curing premixed liquid to prepare a UV light-curing powder treating agent.

[0077] (3) Add a UV light-curing powder treatment agent to powdered alumina (the UV light-curing powder treatment agent is 0.5 wt % of the powdered alumina) at a rotation speed of 70 rpm, stir for 1 hour under UV light conditions, and then bake in an oven at 130° C. for 30 minutes to obtain UV light-cured alumina.

[0078] (4) Vinyl silicone oil (2000 cps) and UV light-cured alumina were mixed in a mass ratio of 20:80 to prepare a high thermal conductivity gel.

[0079] The flow rate and sedimentation test results of the high thermal conductivity gel in Example 1 and Comparative Examples 1-4 are shown in Table 1.

[0080] Table 1

[0081]

[0082] Example 2

[0083] (1) Silane coupling agent A151 and silane coupling agent 570 were uniformly mixed in a ratio of 0.8:1 and then hydrolyzed under the action of alcohol to generate an oligomer powder treatment agent with a certain molecular weight. The amount of water and alcohol added was 5wt% and 15wt% of the total amount of the coupling agent, respectively, to obtain a UV light curing premixed solution;

[0084] (2) Add a certain amount of photoinitiator 819 to the UV light-curing premixed liquid and stir evenly. The amount of photoinitiator 819 added is 0.1 wt % of the UV light-curing premixed liquid to prepare a UV light-curing powder treatment agent.

[0085] (3) Adding a UV light-curing powder treatment agent to powdered boron nitride (the UV light-curing powder treatment agent is 0.1 wt% of powdered aluminum nitride) at a rotation speed of 70 rpm, stirring for 2 h under UV light conditions, and then baking in an oven at 110° C. for 60 min to obtain UV light-cured aluminum nitride.

[0086] (4) Methyl silicone oil and UV light-cured aluminum nitride are mixed in a mass ratio of 20:80 to prepare a high thermal conductive gel.

[0087] Example 3

[0088] (1) Silane coupling agent A172 and silane coupling agent 570 were mixed uniformly in a ratio of 1.2:1 and then hydrolyzed under the action of alcohol to generate an oligomer powder treatment agent with a certain molecular weight. The amount of water and alcohol added was 15wt% and 10wt% of the total amount of the coupling agent, respectively, to obtain a UV light curing premixed solution;

[0089] (2) Add a certain amount of photoinitiator 819 to the UV light-curing premixed liquid and stir evenly. The amount of photoinitiator 819 added is 5wt% of the UV light-curing premixed liquid to prepare a UV light-curing powder treatment agent.

[0090] (3) Adding a UV light-curing powder treatment agent to powdered calcium carbonate (the UV light-curing powder treatment agent is 5 wt % of the powdered calcium carbonate) at a rotation speed of 70 rpm, stirring for 1.5 h under UV light conditions, and then baking in an oven at 120° C. for 50 min to obtain UV light-cured calcium carbonate.

[0091] (4) The hydroxy silicone oil and the UV light-cured calcium carbonate were mixed in a mass ratio of 20:80 to prepare a high thermal conductive gel.

[0092] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0093] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a UV light-curing powder treatment agent, characterized in that: include: The first silane coupling agent and the second silane coupling agent are mixed and subjected to a hydrolysis reaction to obtain an oligomer powder treatment agent; wherein the first silane coupling agent includes any one or more combinations of silane coupling agent 171, silane coupling agent A151, and silane coupling agent A172; and the second silane coupling agent includes silane coupling agent 570; And, the photoinitiator is evenly mixed with the oligomer powder treating agent to prepare a UV light curing powder treating agent.

2. The preparation method according to claim 1, characterized in that: Specifically include: The first silane coupling agent and the second silane coupling agent are mixed and water and alcohol are added, and then a hydrolysis reaction is carried out at 60 to 80° C. for 1 to 2 hours to prepare a UV light-curing premixed liquid containing an oligomer powder treatment agent; And, the photoinitiator is evenly mixed with the UV light-curing premixed liquid to prepare a UV light-curing powder treatment agent.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the first silane coupling agent to the second silane coupling agent is 0.8:1 to 1.2:1; And / or, the mass ratio of the water to the sum of the first silane coupling agent and the second silane coupling agent is 5 to 15:100; And / or, the mass ratio of the alcohol to the sum of the first silane coupling agent and the second silane coupling agent is 5 to 15:100; And / or, the mass ratio of the photoinitiator to the UV light curing premix is ​​0.1-5.0:100; And / or, the oligomer powder treating agent has a structure as shown in formula (I): and / or, the photoinitiator includes photoinitiator TPO and / or photoinitiator 819; And / or, the alcohol comprises ethanol and / or isopropanol.

4. A UV light-curing powder treating agent prepared by the preparation method according to any one of claims 1 to 3.

5. Use of the UV light-curing powder treating agent according to claim 4 in treating powder or preparing high thermal conductivity gel.

6. A method for processing powder, characterized in that: include: The powder is mixed with the UV light-curing powder treatment agent according to claim 4 and stirred for reaction under UV light conditions, and then dried to obtain UV light-curing powder.

7. The processing method according to claim 6, characterized in that: The powder includes any one or more of aluminum oxide, aluminum nitride, magnesium oxide, calcium carbonate, boron nitride, and aluminum hydroxide; And / or, the mass ratio of the powder to the UV light curing powder treating agent is 100:0.1-5.0; And / or, the wavelength of the UV light used is 365-395nm; And / or, the stirring reaction time is 1 to 2 hours; And / or, the drying process is carried out at a temperature of 110 to 130° C. and for a time of 30 to 60 minutes.

8. UV light-cured powder obtained by the treatment method according to claim 6 or 7.

9. A high thermal conductivity gel, characterized in that: include: The base glue and the UV light-curing powder as claimed in claim 8.

10. The high thermal conductivity gel according to claim 9, characterized in that: The mass ratio of the base glue to the UV light curing powder is 20:80 to 3:97; And / or, the base glue includes any one or more combinations of vinyl silicone oil, methyl silicone oil, alkoxy silicone oil, hydroxy silicone oil, and hydrogen-containing silicone oil. And / or, the high thermal conductivity gel further includes an auxiliary agent; the auxiliary agent includes a catalyst and / or an inhibitor; preferably, the catalyst includes a combination of any one or more of a platinum catalyst, chloroplatinic acid, and peroxide; preferably, the inhibitor includes TMDO and / or VMC.

Citation Information

Patent Citations

  • Powder treating agent as well as preparation method and application thereof

    CN118406237A